Determinan Food Waste Rumah Tangga Wilayah Perkotaan dan Perdesaan Kabupaten Bogor: Determinants of Food Waste Among Household in Rural and Urban Areas of Bogor Regency - Lybaws, Lesda; Baliwati, Yayuk Farida; Tanziha, Ikeu (Amerta Nutrition, 2025)
Background: Food Waste (FW) remains a major concern both domestically and globally, with households being the largest contributors. Objectives: This study aimed to determine the total generation of FW in households at risk of stunting and analyze its determinants in urban and rural areas of Bogor Regency. Methods: A quantitative method with a cross-sectional study design was conducted from June to July 2023 in Ciampea and Sukajaya Subsitricts, Bogor Regency. This study involved 168 households as the samples, calculated using the SNI 19-3964-1994 method for sampling and measuring urban waste generation and composition. The inclusion criterion was households with at least one stunting risk factor, according to the National Family Planning Coordination Body or BKKBN. FW determinants included family characteristics and practices (planning, purchasing, storing, cooking, and consuming). The obtained data were then analyzed using chi-square tests and logistic regression. Results: The total FW generated was 5.51 kg/cap/year (urban: 4.08 kg/cap/year; rural: 5.07 kg/cap/year). The most wasted food groups were vegetables and cereals/tubers. Urban households with high income were 4.3 times more likely to generate FW (OR=4.32, CI=1.72 – 10.77). Meanwhile, those with inadequate knowledge were 3.49 times more likely to generate FW (OR=3.49, CI=1.39 – 8.79), and those not planning purchases and processing according to preferences were 4.3 times more likely to generate FW (OR=4.32, CI=1.72 – 10.77). Rural households that did not store food properly were 3.81 times more likely to generate FW (OR=3.81, CI=1.22 – 12.03). Conclusions: The total generation of FW in rural households was higher than in urban households. The determinants of FW in urban areas were income, knowledge, and planning practices, whereas in rural areas, it was storage practices.